Association Mapping of Diastatic Power in UK Winter and Spring Barley by Exome Sequencing of Phenotypically Contrasting Variety Sets - Looseley, Mark E.; Bayer, Micha; Bull, Hazel; Ramsay, Luke; Thomas, William; Booth, Allan; De La Fuente Canto, Carla; Morris, Jenny; Hedley, Pete E.; Russell, Joanne (Frontiers in Plant Science, 2017)
Diastatic Power (DP) is an important quality trait for malt used in adjunct brewing and distilling. Substantial genetic variation for DP exists within UK elite barley cultivars, but breeding progress has been slow due to the limited demand, compared to the overall barley market, and difficulties in assessing DP. Estimates of DP (taken from recommended and national list trials between 1994 and 2012) from a collection of UK elite winter and spring varieties were used to identify contrasting sets of high and low DP varieties. DNA samples were pooled within sets and exome capture sequencing performed. Allele frequency estimates of Single Nucleotide Polymorphisms (SNPs) identified from the sequencing were used to identify genomic locations associated with differences in DP. Individual genotypes were generated from a set of custom KASP assays, both within sets and in a wider germplasm collection, to validate allele frequency estimates and marker associations with DP. QTL identified regions previously linked to variation in DP as well as novel associations. QTL colocalised with a number of genes annotated as having a diastase related function. Results indicate that winter barley is more genetically diverse for genes influencing DP. The marker assays produced by this work represent a resource that is available for immediate use by barley breeders in the production of new high DP varieties.